Beneficiary Satisfaction of the Ekowisata Sungai Hitam Lestari (ESHL) Program by PT Pertamina EP Sangasanga Field from the Perspective of Sustainable Development Goal (SDG) Pillars - Priono, Rodhi Dwi; Pratiwi, Sarah Dhea; Nugraha, Abi Muhammad (Global Writing Academica Researching and Publishing, 2024)
The satisfaction of beneficiaries from an implemented program is a crucial indicator in measuring the effectiveness of the empowerment program. This satisfaction reflects the extent to which the program meets the needs and expectations of the community and their impact on the welfare improvement of the beneficiaries. One of the empowerment programs of the Corporate Social Responsibility (CSR) of PT Pertamina EP Sangasanga Field in Kampung Lama Village, involving the Kelompok Sadar Wisata (Pokdarwis) and Micro, Small, and Medium Enterprises (MSMEs), achieved a Community Satisfaction Index (CSI) score of 95%. However, these results are still statistical and have not been reviewed from the perspective of the four pillars of village Sustainable Development Goals (SDGs). This study aimed to describe the beneficiary satisfaction of the ESHL Program in Kampung Lama Village from the perspective of the four pillars of village SDGs. With this aim, a descriptive qualitative study was conducted by analyzing the archives or documents related to the empowerment program. The analysis was done using the Miles & Huberman method, followed by data validation through data triangulation and corroboration with relevant sources. The results show that all four pillars of the village SDGs are met, both directly and indirectly, regarding social, economic, environmental, legal, and village governance aspects. From planning to execution, the program is seen as mature, resulting in the beneficiaries being highly satisfied with the existing empowerment program.